Monitoreo de insectos vectores del mal de Río Cuarto virus en lotes de avena de Córdoba y La Pampa - Dumon, Analia Delina; Mattio, Maria Fernanda; Pereyra, Nicolas; Torrico Ramallo, Ada Karina; Ruiz Posse, Agustina María; Donadio, Horacio Raul; Genero, Marcela Iris; Franz, Nestor Osvaldo; Denegri, David; Albarracin, Jorge Omar; Corro Molas, Andres Ezequiel; Guillot Giraudo, Walter; et al. (Asociación Argentina de Fitopatólogos, 2022)
Poster